2021
DOI: 10.5937/sjm16-25961
|View full text |Cite
|
Sign up to set email alerts
|

Modelling health care customer satisfaction: Evidence from Serbia

Abstract: Customer loyalty, with satisfaction of customers as its main precondition, has long been regarded as an overarching goal of service businesses. With the proliferation of health care providers, which brought about rising competitive pressures on the market, the issue of how to satisfy and keep patients has been attracting increasing attention of researchers and health care management. Therefore, this study aims to examine the antecedents of patient satisfaction and its direct and mediated impact on patients' be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…We also found that satisfaction mediated the effect of health insurance awareness on trust in the LTCI program. This finding adds new knowledge to the literature which study mediates effect of satisfaction between perceived value and trust in public health insurance ( 21 ) and between healthcare service quality and trust in care providers ( 16 ).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…We also found that satisfaction mediated the effect of health insurance awareness on trust in the LTCI program. This finding adds new knowledge to the literature which study mediates effect of satisfaction between perceived value and trust in public health insurance ( 21 ) and between healthcare service quality and trust in care providers ( 16 ).…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, satisfied insurance enrollees tend to trust their health insurance programs ( 21 ). Increased customer satisfaction results in an increase in the perceived value of insurance programs and an increased willingness to participate in public insurance plans ( 16 ). Based on the positive association between satisfaction and trust in previous studies ( 16 , 21 , 40 ), we proposed the second hypothesis:…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although female physicians demonstrate a higher level of work satisfaction than males (Werdecker and Esch, 2021), this study found that satisfaction was dependent on the physician's age, work experience, and duration of employment in their current institution. Furthermore, patient satisfaction is conditional on positive patient-physician interactions and plays a key role in building long-term relationships (Rajić et al, 2021). This study found that work experience determined how respondents perceived patient satisfaction with the services provided by family medical institutions during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 88%